GPR183 Regulates Interferons, Autophagy, and Bacterial Growth During Mycobacterium tuberculosis Infection and Is Associated With TB Disease Severity - Bartlett, Stacey; Gemiarto, Adrian Tandhyka; Ngo, Minh Dao; Sajiir, Haressh; Hailu, Semira; Sinha, Roma; Foo, Cheng Xiang; Kleynhans, Léanie; Tshivhula, Happy; Webber, Tariq; Bielefeldt-Ohmann, Helle; West, Nicholas P.; et al. (Frontiers in Immunology, 2020)
Oxidized cholesterols have emerged as important signaling molecules of immune function, but little is known about the role of these oxysterols during mycobacterial infections. We found that expression of the oxysterol-receptor GPR183 was reduced in blood from patients with tuberculosis (TB) and type 2 diabetes (T2D) compared to TB patients without T2D and was associated with TB disease severity on chest x-ray. GPR183 activation by 7α,25-dihydroxycholesterol (7α,25-OHC) reduced growth of Mycobacterium tuberculosis (Mtb) and Mycobacterium bovis BCG in primary human monocytes, an effect abrogated by the GPR183 antagonist GSK682753. Growth inhibition was associated with reduced IFN-β and IL-10 expression and enhanced autophagy. Mice lacking GPR183 had significantly increased lung Mtb burden and dysregulated IFNs during early infection. Together, our data demonstrate that GPR183 is an important regulator of intracellular mycobacterial growth and interferons during mycobacterial infection.